Genetic diversity and relationship in American and African oil palm as revealed by RFLP and AFLP molecular markers - Barcelos, Edson; Amblard, Philippe; Berthaud, Julien; Seguin, Marc (Pesquisa Agropecuaria Brasileira, 2002)
The objective of this work was to evaluate the genetic diversity, its organization and the genetic relationships within oil palm (Elaeis oleifera (Kunth) Cortés, from America, and E. guineensis (Jacq.), from Africa) germplasm using Restriction Fragment Length Polymorphism (RFLP) and Amplified Fragment Length Polymorphism (AFLP). In complement to a previous RFLP study on 241 E. oleifera accessions, 38 E. guineensis accessions were analyzed using the same 37 cDNA probes. These accessions covered a large part of the geographical distribution areas of these species in America and Africa. In addition, AFLP analysis was performed on a sub-set of 40 accessions of E. oleifera and 22 of E. guineensis using three pairs of enzyme/primer combinations. Data were subjected to Factorial Analysis of Correspondence (FAC) and cluster analysis, with parameters of genetic diversity being also studied. Results appeared congruent between RFLP and AFLP. In the E. oleifera, AFLP confirmed the strong structure of genetic diversity revealed by RFLP, according to geographical origin of the studied material, with the identification of the same four distinct genetic groups: Brazil, French Guyana/Surinam, Peru, north of Colombia/Central America. Both markers revealed that genetic divergence between the two species is of the same magnitude as that among provenances of E. oleifera. This finding is in discrepancy with the supposed early tertiary separation of the two species